A Comparative Study of Some Motor Abilities Between Three Youth Racket Sport Players (Badminton, Table – Tennis and Tennis - Mohammed, Maher (Journal of Physical Education, 2016)
The importance of the research lies in the training procedures programming and its suitability to the athlete’s individual abilities to reach his/ her best level. The problem of the research lies in not paying enough attention to scientific diagnosis of movement thus not distinguishing between the motor abilities for each of the racket sports. The aim of the research is to identify the differences between some motor abilities (speed, flexibility, agility, and coordination) in racket sports. The subjects were youth racket sport players (badminton, table – tennis, and tennis). The researcher used special ability tests to conclude the variance between racket players (badminton, tennis, and table – tennis) in motor abilities and table – tennis players have speed in hand movement, badminton players have motor flexibility, motor agility while tennis players have higher motor coordination compared to the other racket sport players.